2015
DOI: 10.1007/s10689-015-9789-9
|View full text |Cite
|
Sign up to set email alerts
|

Heterozygous germline mutations in NBS1 among Korean patients with high-risk breast cancer negative for BRCA1/2 mutation

Abstract: The purpose of the present study was to analyze genetic variations in the NBS1 gene and to evaluate the contribution of heterozygous NBS1 mutation to the risk of breast cancer among Korean patients with high-risk breast cancer negative for BRCA1/2 mutation. We screened 235 non-BRCA1/2 Korean patients with high-risk breast cancer for NBS1 mutations. The entire NBS1 gene was sequenced using fluorescent conformation-sensitive capillary electrophoresis. In silico analysis of the NBS1 variants was performed using P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Structure and biochemistry analyses indicate that many tumorigenic mutations of hMrell are primarily associated with its Nbs1 binding and partly with its nuclease activities 119 . A study indicated that heterozygous p.l171V mutation in the Nbs1 gene was found in Korean patients with high-risk breast cancer 121 . In addition, a persistent increase in radiation-induced Nbs1 foci formation was accompanied by an increased frequency of spontaneous chromosome aberrations 122 .…”
Section: Cellular Dna Damage Sensors and Early Signal Transducers In Response To Irmentioning
confidence: 99%
“…Structure and biochemistry analyses indicate that many tumorigenic mutations of hMrell are primarily associated with its Nbs1 binding and partly with its nuclease activities 119 . A study indicated that heterozygous p.l171V mutation in the Nbs1 gene was found in Korean patients with high-risk breast cancer 121 . In addition, a persistent increase in radiation-induced Nbs1 foci formation was accompanied by an increased frequency of spontaneous chromosome aberrations 122 .…”
Section: Cellular Dna Damage Sensors and Early Signal Transducers In Response To Irmentioning
confidence: 99%